Derechos del adulto mayor frente al abandono y maltrato familiar - Maza Peralta, Josselina Roxana (2022)
The present work has been linked to the need to avoid and if possible eradicate, all forms of abuse against older adults, who in general, due to their character of vulnerability, are the ones who suffer most from this kind of harassment by their offspring, although it also comes from the institutions that are in charge of their care and protection. Therefore, all legal and institutional equipment must be activated in order to assert their rights, including with the necessary legal reform so that these purposes can be achieved. The violence and neglect suffered by older adults in the course of their lives responds to a state of "social death" that makes them invisible and excludes them from all forms of development, including the family level, so as a State we must take into consideration the measures that can be achieved to finally achieve the recognition of these, so that these episodes of abuse never plus these episodes of abuse, which can lead to death.